Activity‐based smart AIEgens for detection, bioimaging, and therapeutics: Recent progress and outlook. Issue 4 (7th May 2021) - Li, Haidong; Kim, Heejeong; Han, Jingjing; Nguyen, Van‐Nghia; Peng, Xiaojun; Yoon, Juyoung
Abstract: Activity‐based approaches for designing AIEgens possess prominent advantages including high selectivity, sensitivity, and signal‐to‐noise ratio, and they have received more attention in recent years. Excellent activatable AIE probes have been reported for detecting toxic substances, imaging intracellular active molecules/biomolecules, as well as monitoring the activity of overexpressed enzymes in cancers. Moreover, the majority of activatable theranostic AIEgens can be specifically triggered in cancer cells and can kill these cells under light irradiation, while they have no distinct effect on normal cells, demonstrating satisfactory therapeutic selectivity that is superior to that of traditional chemotherapy. Thus, in this review, we systematically summarized the development of activatable AIE bioprobes in recent years from molecular design principles to biological applications. The challenges of activatable AIE probes and the corresponding solutions are described. We hope that the information provided in this review will facilitate the design of more activatable AIE probes to promote practical application of corresponding AIEgens. Abstract : From molecular design principles to biological applications, we systematically summarized the development of activatable AIE bioprobes in recent years. Additionally, the challenges of activatable AIE probes and the corresponding solutions are described. We hope that the information provided in this review will facilitate the design of more activatable AIE probes to promote practical application of corresponding AIEgens.